(untitled) - Massie, Hugh (Hoboken, N.J., 2006)
Financial DNA? nailed both of us, generating new communication and exciting insights among our team members. It's helping us to grow both personally and professionally. It's more than a good read, it's a virtual experience!
Keywords: Finance, personal,Tài chính, cá nhân